2020
DOI: 10.1007/s11306-020-01703-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining lipidomics and machine learning to measure clinical lipids in dried blood spots

Abstract: Introduction Blood-based sample collection is a challenge, and dried blood spots (DBS) represent an attractive alternative. However, for DBSs to be an alternative to venous blood it is important that these samples are able to deliver comparable associations with clinical outcomes. To explore this we looked to see if lipid profile data could be used to predict the concentration of triglyceride, HDL, LDL and total cholesterol in DBSs using markers identified in plasma. Objectives To determine if DBSs can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…have had reduced recovery and sensitivity from DBSs when compared with wet plasma ( Lakshmy et al, 2012 ; Samuelsson et al, 2015 ; Corso et al, 2016 ). A study by Snowden et al (2020) identified 71% of the lipids found in wet plasma in dried blood spots, which is similar to our results with the PF DPSs in the present study. Additionally, lipid concentrations could be corrected with the use of internal standards, as was done by Snowden et al (2020) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…have had reduced recovery and sensitivity from DBSs when compared with wet plasma ( Lakshmy et al, 2012 ; Samuelsson et al, 2015 ; Corso et al, 2016 ). A study by Snowden et al (2020) identified 71% of the lipids found in wet plasma in dried blood spots, which is similar to our results with the PF DPSs in the present study. Additionally, lipid concentrations could be corrected with the use of internal standards, as was done by Snowden et al (2020) .…”
Section: Discussionsupporting
confidence: 92%
“…A study by Snowden et al (2020) identified 71% of the lipids found in wet plasma in dried blood spots, which is similar to our results with the PF DPSs in the present study. Additionally, lipid concentrations could be corrected with the use of internal standards, as was done by Snowden et al (2020) . Overall, lipid analysis of dried blood and plasma spots shows promise and could be used with field blood samples, without requiring large plasma volumes or cold storage.…”
Section: Discussionsupporting
confidence: 92%
“…This may be because of low sample sizes, lack of interpretability, and general lack of sufficient reference, training, and validation data. Proof of concept ML applications using lipidomics datasets have emerged, for instance for prediction of T2D status (Ho et al, 2020) and to predict clinical lipid concentration from lipid profile data using dried blood spots (Snowden et al, 2020).…”
Section: Ai In Proteomics Data Integrationmentioning
confidence: 99%
“…Lipidomics is of increasing importance in studies of living systems as phospholipids, triglycerides and sterols have various roles in metabolic disease, growth, infection and the structure of biological systems [1][2][3][4][5][6][7][8][9][10][11][12]. Lipidomics is complementary to approaches such as proteomics and transcriptomics, and relatively quick to acquire and therefore cost effective.…”
Section: Introductionmentioning
confidence: 99%